2015
DOI: 10.3998/jmmh.10381607.0009.103
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness, revenge, and adherence to Islam as moderators for psychological wellbeing and depression among survivors of the 1990 Iraqi invasion of Kuwait

Abstract: This study examined the relationships of forgiveness, desire for revenge, adherence to Islam, depression, and psychological wellbeing among 220 Muslim Kuwaiti civilians who experienced the 1990 Iraqi invasion of Kuwait and subsequent seven-month occupation. Participants completed the Enright Forgiveness Inventory (EFI), the Transgression-Related Interpersonal Motivations Inventory-18 (TRIM), the Displaced Aggression Questionnaire (DAQ), the Beck Depression Inventory (BDI), and two sub-scales of Psychological W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
(56 reference statements)
0
7
0
1
Order By: Relevance
“…Internal consistency of the EFI has been reported to range from 0.90 to 0.98 (Enright & Fitzgibbons, ). With respect to concurrent validity, the EFI has been found to correlate positively with other measures of forgiveness such as the Heartland Forgiveness Scale (Thompson & Snyder, ) and the Transgression‐Related Interpersonal Motivations Inventory‐18 (Scull, ). There is also support for the EFI's divergent validity (Enright et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Internal consistency of the EFI has been reported to range from 0.90 to 0.98 (Enright & Fitzgibbons, ). With respect to concurrent validity, the EFI has been found to correlate positively with other measures of forgiveness such as the Heartland Forgiveness Scale (Thompson & Snyder, ) and the Transgression‐Related Interpersonal Motivations Inventory‐18 (Scull, ). There is also support for the EFI's divergent validity (Enright et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Research on Arab and non-Arab Muslim religious coping demonstrates that religiosity does have salutary effects in buffering the effect of stress on psychological outcomes in both Muslim majority and minority contexts. For example, in a study on 220 Muslim Kuwaiti civilians who experienced the 1990 Iraqi invasion of Kuwait and subsequent seven-month occupation, Scull (2015) found that stronger beliefs in Islamic forgiveness and Islamic attitudes were correlated with less desire for revenge, more desire for forgiveness, and better psychological well-being. Likewise, in the migratory context, Adam and Ward (2016) found that for New Zealand Muslims (N = 167), religious practices buffer the effect of acculturative stress on life satisfaction (but not psychological) outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A desire for revenge or vengeance is a common response to redress or remediate a wrong of injustice inflicted on another, and some scholars (e.g., Landes, ; Nisbett & Cohen, ; Victoroff, ) have argued that revenge against an oppressor is an ancient tradition in the Middle East. Indeed, a study of 220 people who were affected by the 1990 Iraqi invasion of Kuwait found that Kuwaitis had relatively low levels of forgiveness and a high desire for revenge against those Iraqis they perceived as the primary transgressor (Scull, ). When people feel transgressed, people may feel justified in seeking vengeance, especially the desire to avenge not oneself but others.…”
Section: Risk Factors For Violent Radicalizationmentioning
confidence: 99%